MACHINE LEARNING-BASED LOAD BALANCING MECHANISMS IN CLOUD COMPUTING: TAXONOMY, CHALLENGES, AND FUTURE DIRECTIONS - Dubey, Utkarsh; Mohd, Wajahat GH; Tuddu, Sanjay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Cloud computing has become the backbone of modern digital infrastructure, offering flexible and scalable access to computing resources. However, uneven workload distribution continues to hinder system efficiency. Conventional load balancing methods such as Round Robin, Min-Min, and various heuristic or metaheuristic techniques often fall short when dealing with large-scale, heterogeneous, and highly dynamic cloud environments. Recent advances in machine learning (ML) have opened new avenues for adaptive and predictive load management. ML-based approaches can forecast workloads, adjust resource allocation, and optimize task scheduling with minimal human intervention. This review presents a structured taxonomy of ML-driven load balancing methods, organized into four main categories: supervised learning, unsupervised learning, deep learning, and reinforcement learning. Key models including artificial neural networks (ANN), convolutional neural networks (CNN), long short-term memory (LSTM) networks, and reinforcement learning agents are analyzed in terms of throughput, latency, energy efficiency, and fault tolerance. Despite significant progress, several issues persist, such as scalability, computational cost, limited data availability, and model interpretability. The paper also discusses emerging directions like explainable AI (XAI), hybrid heuristic-ML models, transfer learning, and integration with edge and fog computing layers. By consolidating recent research, this study aims to guide the development of intelligent, adaptive, and energy-aware load balancing strategies for future cloud ecosystems.